Peran media sosial marketing dan diskon dalam meningkatkan minat beli konsumen pada En Florist Bouquets Cileungsi - Zainuri, Zainuri; Wibowo, Yudi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2026)
This research aims to analyze the role of social media marketing and discounts in increasing consumer purchase intention at En Florist Bouquets Cileungsi. The study employed a qualitative method with a descriptive approach. Data were collected through interviews with the business owner, management team, and consumers, supported by observation and documentation. The findings indicate that social media marketing plays a crucial role in building brand image, creating closer connections with consumers, and enhancing product attractiveness through aesthetic, consistent, and interactive content. Furthermore, discounts are proven to influence purchasing decisions, determined by the size of the discount, the duration of the promotion, and the type of products selected. Percentage-based discounts are more appealing for higher-priced products, while nominal discounts are more attractive for affordable items. Short-term promotions such as flash sales are also effective in encouraging immediate purchases. In conclusion, the study highlights that the implementation of social media marketing and discount strategies significantly contributes to increasing consumer purchase intention while strengthening the competitiveness of En Florist Bouquets.